OP0026 Induction of Clinical Remission Followed by Drug-Free Withdrawal with Abatacept Combination and Monotherapy in Early RA: Results from the AVERT Study over 18 Months. (10th June 2014) - Emery, P.; Burmester, G.; Bykerk, V.; Combe, B.; Furst, D.E.; Barre, E.; Karyekar, C.S.; Wong, D.; Huizinga, T.W.
Abstract : Background: AVERT (A ssessing V ery E arly R heumatoid arthirits T reatment) is a Phase IIIb, randomized, active-controlled study to evaluate the efficacy and safety of subcutaneous (SC) abatacept (ABA) in pts with early RA. Objectives: To assess ABA + MTX or ABA monotherapy in inducing clinical remission at 12 mths and then maintain it following rapid withdrawal of all RA treatment (biologics, DMARDs, steroids) in pts with early RA. Methods: MTX-naïve, anti-CCP2+ pts with early RA (active synovitis in ≥2 joints for ≥8 wks, DAS28 (CRP) >3.2 and onset of symptoms within ≤2 yrs) were included. Pts were randomized to 12 mths of weekly SC ABA 125 mg + MTX, ABA 125 mg monotherapy or MTX alone. Pts with DAS28 (CRP) <3.2 at Mth 12 entered a 12-mth withdrawal period with no treatment. All pts with protocol-defined flare after Mth 15 could receive open-label ABA + MTX. The co-primary endpoints compared ABA + MTX and MTX alone in pts achieving DAS28 (CRP) <2.6 at (1) 12 mths and (2) both 12 and 18 mths. ABA monotherapy was also assessed. Results: 351 pts (n=119, 116 and 116 pts in the ABA + MTX, ABA and MTX arms, respectively) with early RA, highly active disease and poor prognosis (at baseline: mean RA duration of 0.56 yrs, mean DAS28 (CRP) of 5.4, mean HAQ of 1.4; 95.2% RF+ and anti-CCP2+) entered the study. At 12 mths, 60.9, 42.5 and 45.2% achieved DAS28 (CRP) <2.6 (ABA + MTX, ABA and MTX, respectively). Odds ratio (OR; 95% CI) for ABA + MTX vs MTX: 2.01 (1.18, 3.43) with p=0.01 and for ABA vs MTX: 0.92 (0.55, 1.57). At most time points, efficacy on signs and symptoms in the ABA monotherapy arm fell between the ABA + MTX and MTX arms (Figure) based on DAS28 (CRP) as well as other measures. Following treatment withdrawal, most pts discontinued due to increase in disease activity (177/223; 79.4%). Rates of pts achieving DAS28 (CRP) <2.6 at both 12 and 18 mths were 14.8, 12.4 and 7.8% for ABA + MTX, ABA and MTX, respectively; OR (95% CI) for ABA + MTX vs MTX: 2.51 (1.02, 6.18), p=0.045 and for ABA vs MTX: 2.04 (0.81, 5.14). In a post hoc analysis, pts who maintained DAS28 (CRP) <2.6 at both Mth 12 and 18 tended to have numerically lower baseline mean symptom duration, DAS28 (CRP), HAQ score and DAS28 (CRP) <2.6 over time during the treatment period compared with pts who achieved only DAS28 (CRP) <2.6 at 12 mths. Over 12 mths of treatment, the number (%) of serious adverse events was 8 (6.7), 14 (12.1) and 9 (7.8) and the number (%) of serious infections was 1 (0.8), 4 (3.4) and 0 in the ABA + MTX, ABA and MTX arms, respectively. Conclusions: In this study, in pts with highly active early RA with poor prognosis, abatacept + MTX resulted in significantly higher rates of remission and comparable safety vs MTX alone at 12 mths. At most time points, abatacept monotherapy was more effective than MTX alone. A small but significantly higher number of patients treated with abatacept + MTX were able to maintain drug-free remission compared to MTX. Disclosure of Interest: P. Emery Grant/research support: AbbVie, BMS, Merck, Pfizer, Roche, Consultant for: AbbVie, BMS, Merck, Pfizer, Roche, Takeda, G. Burmester Grant/research support: BMS, AbbVie, Pfizer, Medimmune, Novartis, Roche, UCB, Lilly, Consultant for: BMS, AbbVie, Pfizer, MSD, Medimmune, Roche, UCB, Speakers bureau: BMS, AbbVie, Pfizer, MSD, Roche, UCB, V. Bykerk Grant/research support: Amgen, Pfizer, BMS, Janssen, UCB, Roche/Genentech, B. Combe Grant/research support: Pfizer, Roche-Chugai, Speakers bureau: BMS, Merck, Pfizer, Roche-Chugai, UCB, D. Furst Grant/research support: AbbVie, Actelion, Amgen, BMS, Gilead, GSK, NIH, Novartis, Pfizer, Roche/Genentech, UCB, Consultant for: AbbVie, Actelion, Amgen, BMS, Janssen, Gilead, GSK, NIH, Novartis, Pfizer, Roche/Genentech, UCB, Speakers bureau: AbbVie, Actelion, UCB, E. Barre Employee of: BMS, C. Karyekar Employee of: BMS, D. Wong Employee of: BMS, T. Huizinga Grant/research support: EU & Dutch Arthritis Foundation, Consultant for: Abbott Laboratories, Biotest AG, Bristol-Myers Squibb, Crescendo Bioscience, Inc, Novartis Pharmaceuticals Corporation, Pfizer Inc, Roche, sanofi-aventis, Schering-Plough, UCB, Inc., Eli Lilly, Speakers bureau: Abbott Laboratories, Biotest AG, Bristol-Myers Squibb, Novartis Pharmaceuticals Corporation, Pfizer Inc, Roche, sanofi-aventis, Schering-Plough DOI: 10.1136/annrheumdis-2014-eular.2132